Diclofenac (DCF) as an emerging pollutant: Occurrence, ecotoxicity, and biodegradation strategies - Ahmed Sayed Badawy; Ying Xu; Hao Ren; Zhenmei Lu (Ecotoxicology and Environmental Safety, 2025)
Diclofenac (DCF) is a non-steroidal anti-inflammatory drug with analgesic and antipyretic effects. It is an emerging pollutant that has attracted global attention due to its widespread distribution in various ecosystems and its potential risk to human and non-target organisms, such as aquatic organisms, plants, animals, and microorganisms. It also contributes to the spread of antibiotic-resistant pathogens and the formation of new pollutants through its interaction with other contaminants. This comprehensive review highlights the occurrence, fate, and concentration of DCF across environmental compartments and relates the mode of toxicity, level of exposure, and route of administration as a unique approach for addressing the destructive consequence of DCF in different ecosystems. Finally, the mitigation strategy to eradicate the DCF toxicity through bioremediation is critically discussed, focusing on the diversity of DCF-degrading microorganisms, biodegradation pathways, and underlying molecular mechanisms to provide a comprehensive overview of DCF biodegradation.